PSYCHOLOGICAL ASPECTS OF THE MANAGEMENT EFFECTIVENESS IN CRISIS SITUATIONS - Орап, Марина (Modern engineering and innovative technologies, 2024)
The article presents the results of a theoretical and empirical study of the effectiveness of management activities in crisis situations. The topic is relevant in connection with Russia’s full-scale invasion of Ukraine, which required managers to actively